The productivity of Australia's railways in the 20th century - consequences for a growing, sustainable industry - Wills-Johnson, Nick (2007)
Railways offer significant potential to provide sustainable transport solutions, particularly for freight, in an environment where climate change is becoming increasingly important. To do this, however, they need to remain competitive with other modes of transport, and this requires productivity growth. The more productive railways can become, the better their competitiveness with other transport modes and the better they can perform their role in sustainable transport for the future. The Planning and Transport Research Centre is currently constructing a database covering the economic aspects of Australia's railways from Federation to the present day. This paper draws upon an early version of this database to calculate total factor productivity indices for Australia's railways, highlighting an important aspect of railway history in Australia. Two indices, allowing comparison within railways across time, and across railways, are constructed. From an analysis of productivity growth through the century and its causes, the paper draws some initial conclusions about policy directions to assist in ensuring the future sustainability of the industry.